Standardizing blue ling landings per unit effort from industry haul-by-haul data using generalized additive models - Lorance, Pascal; Pawlowski, Lionel; Trenkel, Verena M. (ICES Journal of Marine Science, 2010)
Abstract Lorance, P., Pawlowski, L., and Trenkel, V. M. 2010. Standardizing blue ling landings per unit effort from industry haul-by-haul data using generalized additive models. – ICES Journal of Marine Science, 67: 1650–1658. Haul-by-haul data derived from skippers' personal logbooks, from the French deep-water fishery to the west of the British Isles, were used to calculate standardized blue ling (Molva dypterygia) landings per unit effort (lpue) for the period 2000–2008. Lpue values were estimated using generalized additive models with depth, vessel, statistical rectangle, area, and year as explanatory variables. Because of their statistical distribution, landings were modelled by a Tweedie distribution, which allows datasets to contain many zeros. To investigate how to track stock trends reliably, lpue values were estimated in five areas for different subsets of the data. The subsets consisted of hauls during the spawning season (when blue ling aggregate), outside the spawning season, and hauls in which blue ling was only a bycatch. The results suggest that blue ling lpue values have been stable over the period 2000–2008, and that the declining trend previously observed for the stock has been halted. This finding is consistent with stable mean lengths in the landings during the same period. The study demonstrates the greater suitability of haul-by-haul data than EC logbook data for deriving abundance indices for deep-water stocks.